Elucidating the role of pyrimidine metabolism in prostate cancer and its therapeutic implications - Liang Huang; Yu Xie; Shusuan Jiang; Kan Liu; Zhihao Ming; Hong Shan (Scientific Reports)
Abstract Our study aims to investigate the role of pyrimidine metabolism in prostate cancer and its associations with the immune microenvironment, drug sensitivity, and tumor mutation burden. Through transcriptomic and single-cell RNA sequencing analyses, we explored metabolic pathway enrichment, immune infiltration patterns, and differential gene expression in prostate cancer samples. The results showed that pyrimidine metabolism-related genes were significantly upregulated in the P2 subgroup compared to the P1 subgroup, with enhanced metabolic activity observed in basal and luminal epithelial cells. In addition, immune infiltration analysis revealed a strong correlation between pyrimidine metabolism and immune cell regulation, particularly involving T cell activity. Tumors in the P2 subgroup, characterized by higher pyrimidine metabolism, exhibited greater infiltration of activated CD4 + T cells and M2 macrophages, indicating a potential link between metabolic reprogramming and the immune response in prostate cancer. Drug sensitivity analysis further demonstrated that tumors with elevated pyrimidine metabolism displayed increased responsiveness to several chemotherapeutic agents, including BI-2536, JW-7-24-1, and PAC-1, suggesting that targeting pyrimidine metabolism may enhance treatment efficacy. Moreover, key genes involved in pyrimidine de novo synthesis, such as RRM2, were identified as potential drivers of tumor progression, providing new insights into the molecular mechanisms underlying aggressive prostate cancer phenotypes. In conclusion, pyrimidine metabolism plays a critical role in prostate cancer progression, influencing immune infiltration and drug sensitivity. Targeting this metabolic pathway offers a promising strategy for the development of new therapeutic approaches, particularly for overcoming drug resistance and improving outcomes in patients with advanced prostate cancer.